Challenges of Beekeeping in Arid Regions - Salim Hitouche; Mohamed Ridha Messak; Azzouzi Imane; Messaoud Lazereg (SocioEconomic Challenges)
This study examines the beekeeping practices in the arid Ziban region of Algeria, which is characterized by significant geographical variability. It is primarily concentrated in the northern part of the country, where the climate and honey resources are more favorable. Its aim is to elucidate the behaviors of beekeepers and the challenges they encounter in ensuring the sustainability of beekeeping in this area, facing different challenges related to climate change, public subsidies, and pesticide pressure. Due to the lack of official data categorizing farmers practicing beekeeping, our sample was formed using a simple probabilistic method and comprises 41 beekeepers out of the 93 identified by local administration (DSA). A detailed questionnaire was administered between April and May 2023. To minimize misunderstandings, the questionnaire was prepared in both Arabic and French and was conducted face-to-face with the selected beekeepers. Due to availability issues and time constraints, beekeepers that were unable to attend scheduled meetings via telephone also reached out. A semi-structured survey was conducted involving 41 local beekeepers and a descriptive analysis of the qualitative and quantitative data gathered. Data analysis and coding were executed using open-source R-Studio software. The findings indicate a significant potential for the growth of beekeeping in the Ziban region. However, there has been minimal intervention aimed at improving existing practices and assisting beekeepers in overcoming the challenges they face in sustaining their activities, coupled with minimal technical support from public authorities to enhance existing practices and encourage beekeepers to address sustainability challenges. The beekeeping sector in the Ziban region is constrained by various obstacles, with the most critical being logistical issues, a shortage of beekeeping equipment, pesticide exposure, climate change, and elevated production costs. Also, it is essential for public authorities to address these challenges with local stakeholders to ensure the future viability of beekeeping.